Metal Mobilization From CO2 Storage Cap-Rocks: Experimental Reactions With Pure CO2 or CO2 SO2 NO - Pearce, J. K.; Dawson, G. W.; Southam, G.; Paterson, D.; Kirste, D.; Golding, S. D. (Frontiers in Energy Research, 2022)
CO2 geological storage will be needed as part of the transition to lower greenhouse gas emissions. During CO2 storage the mobilisation of metals from minerals to formation water via CO2 water rock reactions may be a concern for water quality. The sources, behaviour, and fate of metals, however, are not well understood. Metals in minerals of calcite cemented sandstone, feldspar-rich sandstone, and ironstone seal drill cores from a target storage site were characterised. The cores were reacted with low salinity water and pure supercritical CO2 or impure CO2 with SO2 and nitric oxide (NO), at reservoir conditions. Calcite cemented core underwent calcite dissolution with chlorite, plagioclase, and sulphide alteration. The highest concentrations of calcium, and manganese were released in the reaction of calcite cemented sandstone seal, with the lowest mobilised arsenic concentration. Pure CO2 reaction of the feldspar-rich sandstone seal resulted in calcite dissolution, with plagioclase, chlorite, kaolinite, illite and sulphides corroded. Impure CO2 reaction of the feldspar-rich sandstone led to additional corrosion of apatite, pyrite, and sphalerite cements. Generally, dissolved iron, lead, zinc, and arsenic were released, then re-precipitated in oxide minerals, or adsorbed. Calcium, manganese, and strontium were released primarily from calcite cement dissolution. Plagioclase corrosion was a second source of dissolved strontium, and chlorite dissolution a second source of manganese. Although sulphides contained higher concentrations of metals, the higher reactivity of carbonates meant that the latter were the main sources contributing to dissolved metal concentrations. The mineral content of the seal cores, and the injected gas mixture, had an impact on the type and concentration of metals released. The ubiquitous presence of carbonate minerals means that this study is applicable to understanding the potential risk factors for water quality changes, and the mobilisation and fate of environmentally regulated metals, in both CO2 storage complexes, and overlying drinking water aquifers worldwide.